MO505: Prevalence of Lupus Nephritis Among Patients With Systemic Lupus Erythematosus In Germany. (3rd May 2022) - Hunnicutt, Jake; Schultze, Michael; Garal-Pantaler, Elena; Pignot, Marc; Elizabeth Georgiou, Mary; Gairy, Kerry
Abstract: BACKGROUND AND AIMS: Lupus nephritis (LN) is the most common severe manifestation of systemic lupus erythematosus (SLE) and can lead to end-stage renal disease and death. However, there are limited data to contextualize the burden of LN in Germany, with no published studies using national claims data. This cross-sectional study aimed to estimate the annual prevalence of SLE and LN from 2011–17 using claims data from the Betriebskrankenkassen (BKK) German Sickness Fund Database. METHOD: For each study year (2011–17), three patient populations were identified using International Classification of Diseases, Tenth Revision, German Modification (ICD-10-GM) codes: (1) Patients with SLE (≥1 SLE inpatient claim or ≥1 outpatient claim with a confirmatory claim in a separate quarter within ± 3 years); (2) Patients with LN, sensitive definition (based on the presence of SLE [as above] with ≥ 1 nephritis claim within ± 1 year from the initial SLE claim) and (3) Patients with LN, specific definition (based on the presence of SLE [as above] with ≥ 2 nephritis claims in separate quarters within ± 1 year from the initial SLE claim). For each year, the annual prevalence of SLE and LN/100 000 was estimated by dividing the number of patients identified in each population by the number of individuals insured in the database in that year. The proportion of SLE patients with LN was also estimated. To estimate the total number of patients with SLE and LN in Germany by age and sex standardization, the German statutory health insurance (SHI) system (covering 87% of the German population) was used to extrapolate from the prevalence calculated in the BKK database. RESULTS: Approximately 5 million patients were insured in the BKK database between 2011–17; the ratio of insured males to females was ∼1:1 throughout the study period. The annual prevalence of SLE and LN/100 000 increased from 2011 (SLE, 37.68; LN sensitive, 12.79; LN specific, 9.99) to 2017 (SLE, 54.74; LN sensitive, 19.06; LN specific, 15.16) (Fig. 1 ). In 2017, the ratio of males to females/100 000 patients was ∼1:5.5 for the SLE cohort, 1:4.5 for the LN-sensitive cohort and 1:4.4 for the LN-specific cohort. The proportion of SLE patients with LN remained consistent across the study period, ranging from 26.51% (specific definition) and 33.96% (sensitive definition) in 2011 to 27.69% and 34.82%, respectively, in 2017. When extrapolating the prevalence estimates to the wider German SHI system, the estimated number of SLE patients was >41 000 in 2017, with the total LN patient population ranging from 11 515 (specific definition) to 14 483 (sensitive definition) (Fig. 2 ). CONCLUSION: The prevalence of LN increased between 2011 and 2017 among patients insured in the BKK database and is estimated to impact >11 000 patients in the wider German SHI system. Limitations include an absence of renal biopsy information and the inability to distinguish patients with active nephritis from those with historical or inactive LN based on clinical parameters. Nonetheless, these data highlight the prevalence of LN among patients with SLE and the need for effective screening and disease management to improve patient outcomes. Further work to understand the treatment and economic burden of LN among patients with SLE in Germany is ongoing.